2009
DOI: 10.5088/atl.2009.31.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição espacial e variações temporais da abundância de ovos e larvas de Micropogonias furnieri no estuário da Lagoa dos Patos: registros históricos e forçantes ambientais

Abstract: -96201-900 -Rio Grande -RSBrasil. 2 docbruno@furg.br RESUMO As espécies de peixes que ocorrem no estuário da Lagoa dos Patos (ELP) apresentam diferentes estratégias de desova que procuram otimizar um balanço entre condições ambientais locais e remotas, e seu ciclo de vida. O presente trabalho descreve e analisa a distribuição espacial, variabilidade temporal e a influência de variáveis ambientais sobre a abundância de ovos e larvas de Micropogonias furnieri no ELP. Foram utilizadas variáveis ambientais e um ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Previous studies on the early life history of the sciaenids off Southern and Southeastern Brazil include those by Matsuura and Nakatani (1979) who described the development of larval Umbrina coroides Cuvier, 1830 near Anchieta island; Sinque (1980) who studied the larval and juvenile development of Cynoscion leiarchus (Cuvier, 1830), Menticirrhus americanus, Micropogonias furnieri, Stellifer rastrifer, Macrodon ancylodon (Bloch & Schneider, 1801) and Isopisthus parvipinnis (Cuvier, 1830) in the Cananéia-Iguape estuary; Katsuragawa et al (1993) who described the larval distribution of Menticirrhus americanus at Ubatuba; Godefroid et al (2001) who described the larval and juvenile occurrence of Menticirrhus americanus, Menticirrhus littoralis (Holbrook, 1847), Umbrina coroides and Micropogonias furnieri in the Pontal do Sul region; Bruno and Muelbert (2002;2009) who investigated the distribution and abundance patterns of eggs and larvae of Micropogonias furnieri in the Patos lagoon, and Itagaki et al (2007) who described the larval and juvenile development of Bairdiella ronchus (Cuvier, 1830) in the Cananéia-Iguape estuary. However, no studies on early sciaenids have been undertaken in the estuarine and coastal area around Santos.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the early life history of the sciaenids off Southern and Southeastern Brazil include those by Matsuura and Nakatani (1979) who described the development of larval Umbrina coroides Cuvier, 1830 near Anchieta island; Sinque (1980) who studied the larval and juvenile development of Cynoscion leiarchus (Cuvier, 1830), Menticirrhus americanus, Micropogonias furnieri, Stellifer rastrifer, Macrodon ancylodon (Bloch & Schneider, 1801) and Isopisthus parvipinnis (Cuvier, 1830) in the Cananéia-Iguape estuary; Katsuragawa et al (1993) who described the larval distribution of Menticirrhus americanus at Ubatuba; Godefroid et al (2001) who described the larval and juvenile occurrence of Menticirrhus americanus, Menticirrhus littoralis (Holbrook, 1847), Umbrina coroides and Micropogonias furnieri in the Pontal do Sul region; Bruno and Muelbert (2002;2009) who investigated the distribution and abundance patterns of eggs and larvae of Micropogonias furnieri in the Patos lagoon, and Itagaki et al (2007) who described the larval and juvenile development of Bairdiella ronchus (Cuvier, 1830) in the Cananéia-Iguape estuary. However, no studies on early sciaenids have been undertaken in the estuarine and coastal area around Santos.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the number of individuals, we noticed that nearly 71% of the total number of individuals was sampled in spring, although the biomasses of both seasons are nearly 50% of the total weight. This shows that there are more individuals relatively smaller in spring than in autumn, which may indicate a possible reproductive season for at least some of the species (e.g., Araújo & Santos, 1999;Bernardes & Dias, 2000;Robert & Chaves, 2001;Castello & Castello, 2003;Godefroid et al, 2004;Lima & Castello, 2007;Bruno & Muelbert, 2009). As for the biomass, approximately 71% of the total weight was sampled in 1990 although the number of individuals did not differ much between the two years.…”
Section: Discussionmentioning
confidence: 87%
“…Despite the strong seasonal pattern in recruitment of fish eggs and larvae to the Patos Lagoon estuary, long‐term studies suggest the existence of decadal variations in climate due to El Niño Southern Oscillation (Muelbert et al ., ). El Niño (high precipitation) and La Niña (low precipitation) events interact with wind patterns in the region and influence the salinity in this ecosystem and consequently control the occurrence and abundance of fish eggs and larvae (Bruno and Muelbert, ). Despite these disturbances, the study period showed consistent patterns in salinity and consequently in the recruitment of such early life stages of fishes into the Patos Lagoon estuary (Muelbert et al ., ).…”
Section: Discussionmentioning
confidence: 99%